A symbiotic gene stimulates aggressive behavior favoring the survival of parasitized caterpillars - Zhiwei Wu; Xiaotong Wu; Zhizhi Wang; Xiqian Ye; Lan Pang; Yanping Wang; Yuenan Zhou; Ting Chen; Sicong Zhou; Zehua Wang; Yifeng Sheng; Qichao Zhang; et al. (Proceedings of the National Academy of Sciences, 2025)
Animals often exhibit increased aggression in response to starvation, while parasites often manipulate host behavior. In contrast, underlying molecular mechanisms for these behavioral changes are mostly unknown. The diamondback moth, Plutella xylostella , is an agricultural pest that feeds on cruciferous plants as larvae, while Cotesia vestalis is a parasitoid wasp that parasitizes diamondback moth larvae. In this study, we determined that unparasitized diamondback moth larvae exhibit increased aggression and cannibalism when starved, while starved larvae parasitized by C. vestalis were more aggressive than unparasitized larvae. C. vestalis harbors a domesticated endogenized virus named Cotesia vestalis bracovirus (CvBV) that wasps inject into parasitized hosts. Starvation increased octopamine (OA) levels in the central nervous system (CNS) of diamondback moth larvae while a series of experiments identified a CvBV-encoded gene product named Assailant that further increased aggression in starved diamondback moth larvae. We determined that Assailant increases OA levels by activating tyramine beta-hydroxylase ( PxTβh ), which is a key enzyme in the OA biosynthesis pathway. Ectopic expression of assailant in Drosophila melanogaster likewise upregulated expression of DmTβh and OA, which increased aggressive behavior in male flies as measured by a well-established assay. While parasitized hosts are often thought to be at a competitive disadvantage to nonparasitized individuals, our results uncover how a parasitoid uses an endogenized virus to increase host aggression and enhance survival of offspring when competing against unparasitized hosts.